(untitled) (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
Web-Based Augmented Reality (AR) is an emerging interactive technology that is increasingly adopted in the fields of visual communication design and digital education. This study aims to analyze trends in the use of Web-Based AR within interactive design contexts and to identify user preferences regarding its features. The research employs a literature review and secondary data analysis, drawing from academic publications, industry reports, and online surveys conducted between 2019 and 2024. The findings reveal a significant increase in the adoption of Web-Based AR both globally and in Indonesia. Key factors driving adoption include interactivity without installation, cross-device compatibility, and rapid browser-based access. Trend diagrams, comparative tables of AR platforms (such as 8thWall, ZapWorks, and WebXR API), and user preference visualizations are presented to support the analysis. The study discusses technological challenges, adoption gaps, and design implications, particularly in education and marketing. Limitations include reliance on secondary data and limited geographic scope. The study’s outcomes are expected to serve as a reference for interactive content developers, educators, and researchers in designing inclusive and adaptive AR-based user experiences.